Prevalence and comorbidity of allergic diseases in preschool children - Hyeong Yun Kim; Eun Byul Kwon; Ji Hyeon Baek; Youn Ho Shin; Hye Yung Yum; Hye Mi Jee; Jung Won Yoon; Man Yong Han (Korean Pediatric Society, 2013)
PurposeAllergic disease and its comorbidities significantly influence the quality of life. Although the comorbidities of allergic diseases are well described in adult populations, little is known about them in preschool children. In the present study, we aimed to assess the prevalence and comorbidity of allergic diseases in Korean preschool children.MethodsWe conducted a cross-sectional study comprising 615 Korean children (age, 3 to 6 years). Symptoms of allergic diseases were assessed using the Korean version of the International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire that was modified for preschool children. Comorbidities of allergic diseases were assessed by 'In the last 12 months, has your child had symptoms?'.ResultsThe prevalence of symptoms of asthma, allergic rhinitis, and atopic dermatitis as recorded using the ISAAC questionnaire, within the last 12 months was 13.8%, 40.7%, and 20.8%, respectively. The symptom rates of allergic conjunctivitis, food allergy, and drug allergy were 14.8%, 10.4%, and 0.8%, respectively. The prevalence of allergic rhinitis in children with asthma was 64.3% and that of asthma in children with allergic rhinitis was 21.6%. The prevalence of rhinitis in children with conjunctivitis was 64.8% and that of conjunctivitis in children with rhinitis was 23.6%.ConclusionThe prevalence of current rhinitis in our preschool children is shown to be higher than that previously reported. Allergic conjunctivitis is closely associated with asthma and allergic rhinitis. However, further studies are warranted to determine the prevalence and effects of these comorbidities on health outcomes in preschool children.